Double-negative feedback between S-phase cyclin-CDK and CKI generates abruptness in the G1/S switch - Venta, Rainis; Valk, Ervin; Kõivomägi, Mardo; Loog, Mart (Frontiers in Physiology, 2012)
The G1/S transition is a crucial decision point in the cell cycle. At G1/S, there is an abrupt switch from a state of high CDK inhibitor (CKI) levels and low S-phase CDK activity to a state of high S-phase CDK activity and degraded CKI. In budding yeast, this transition is triggered by phosphorylation of the Cdk1 inhibitor Sic1 at multiple sites by G1-phase CDK (Cln1,2-Cdk1) and S-phase CDK (Clb5,6-Cdk1) complexes. Using mathematical modeling we demonstrate that the mechanistic basis for the abruptness and irreversibility of the G1/S transition is the highly specific phosphorylation of Sic1 by S-phase CDK complex. This switch is generated by a double negative feedback loop in which S-CDK1 phosphorylates Sic1, thus targeting it for destruction, and thereby liberating further S-CDK1 from the inhibitory Sic1-S-CDK1 complex. Our model predicts that the abruptness of the switch depends upon a strong binding affinity within the Sic1-S-CDK inhibitory complex. In vitro phosphorylation analysis using purified yeast proteins revealed that free Clb5-Cdk1 can create positive feedback by phosphorylating Sic1 that is bound in the inhibitory complex, and that Sic1 inhibits Clb5-Cdk1 with a sub-nanomolar inhibition constant. Our model also predicts that if the G1-phase CDK complex is too efficient at targeting Sic1 for destruction, then G1/S becomes a smooth and readily reversible transition. We propose that the optimal role for the G1-phase CDK in the switch would not be to act as a kinase activity directly responsible for abrupt degradation of CKI, but rather to act as a priming signal that initiates a positive feedback loop driven by emerging free S-phase CDK.